Role of PI3K-AKT-mTOR and Wnt Signaling Pathways in Transition of G1-S Phase of Cell Cycle in Cancer Cells - VADLAKONDA, LAKSHMIPATHI; Pasupuleti, Mukesh; Reddanna, Pallu (Frontiers in Oncology, 2013)
The PI3K–Akt pathway together with one of its downstream targets, the mechanistic target of rapamycin (mTOR) is a highly deregulated pathway in cancers. There is a reciprocal relation between the Akt phosphorylation and mTOR complexes. Akt phosphorylated at T308 activates mTORC1 by inhibition of the tuberous sclerosis complex (TSC1/2), where as mTORC2 is recognized as the kinase that phosphorylates Akt at S473. Recent developments in the research on regulatory mechanisms of autophagy places mTORC1 mediated inhibition of autophagy at the central position in activation of proliferation and survival pathways in cells. Autophagy is a negative regulator of Wnt signaling pathway and the downstream effectors of Wnt signaling pathway, cyclin D1 and the c-Myc, are the key players in initiation of cell cycle and regulation of the G1-S transition in cancer cells. Production of reaction oxygen species (ROS), a common feature of a cancer cell metabolism, activates several downstream targets like the transcription factors FoxO, which play key roles in promoting the progression of cell cycle. A model is presented on the role of PI3K -Akt - mTOR and Wnt pathways in regulation of the progression of cell cycle through Go-G1-and S phases.